1996
DOI: 10.4269/ajtmh.1996.55.150
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Growth of School-Aged Children with Schistosomiasis and Geohelminth Infection

Abstract: Light or moderate intensity infection with Schistosoma mansoni may contribute to growth deficits. We report on the effects of treatment for S. mansoni on growth and development in Brazilian schoolchildren. Anthro pometric measurements were taken from 539 S. mansoni-infected children and their age-and sex-matched egg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
60
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 12 publications
8
60
2
1
Order By: Relevance
“…This result might be due to the lower socioeconomic status of shantytown community and can reflect a broad range of insults such as poverty, ignorance, large family size and inadequate utilisation at the household level in slum dwellers (Kan, 1993). The data also indicated that the boys were thinner than girls in shantytown schools conforming to the study that indicated that the boys were more vulnerable to chronic unfavourable conditions such as infections or disease (Parraga et al, 1996).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This result might be due to the lower socioeconomic status of shantytown community and can reflect a broad range of insults such as poverty, ignorance, large family size and inadequate utilisation at the household level in slum dwellers (Kan, 1993). The data also indicated that the boys were thinner than girls in shantytown schools conforming to the study that indicated that the boys were more vulnerable to chronic unfavourable conditions such as infections or disease (Parraga et al, 1996).…”
Section: Discussionmentioning
confidence: 78%
“…Although the boys had a higher stunting rate than girls in shantytown schools, in apartment schools, they did not. It is suggested that growth in boys may be more sensitive to environmental insults such as infections and diseases (Parraga et al, 1996). Previous studies reported that diarrhoeal diseases, amoebal dysenteric diseases and enteric fever infections were prevalent in the shantytown community (Ulukanligil et al, 2001a, b).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, when analyzed alone or when independent of other risk factors, intestinal helminths may not seem to be a major factor in nutritional deficits, as has been the conclusion of this group in some previous studies. 27,28 A limitation of our cross-sectional study is that it is impossible to determine if polyparasitism proceeds or follows anemia. Therefore, causation cannot be attributed to polyparasitism.…”
Section: Discussionmentioning
confidence: 99%
“…All measurements were carried out using standard anthropometric methods as described previously. 13,14 For each child measurement of weight, height, skinfold thicknesses, and arm circumference were made. Indices were calculated and converted to Z-scores for analysis.…”
Section: Methodsmentioning
confidence: 99%